La genèse de The Souls of Black Folk : le chapitre initial de la vie intellectuelle de W. E. B. Du Bois, 1885-1903 - Dufour-Lauzon, Émilie (Université de Montréal, 2016)
William Edward Burghardt Du Bois published The Souls of Black Folk in 1903. Du Bois pursued three different goals when he wrote his masterpiece. First, he argued that Booker T. Washington’s strategy of trading political rights for economic opportunities was not the best way to improve the condition of African Americans. Second, Du Bois highlighted the accomplishments and distinctive abilities of his people in order to undermine the pretended biological and moral superiority of Whites that often justified the pushback against equal rights for all. Third, Du Bois wished to inspire Americans to become better citizens by compelling his fellow countrymen to embrace the Founding Fathers’ ideals and higher moral standards. The writing of The Souls of Black Folk marks an important shift in Du Bois’ intellectual life because he recants the accommodationist rhetoric of his youth during this period. Some of the ideas introduced in The Souls of Black Folk can be traced back to the influence of Alexander Crummell and of Du Bois’ teachers at the University of Berlin. However, it is Du Bois’s field work in the black community of Philadelphia that made him realize both the degree of the inequalities faced by African Americans and the fact that hard work and enthusiasm are not enough to overcome such significant disparities.
Keywords: African Americans; Afro-américains; Booker T. Washington; History - United States / Histoire - États-Unis (UMI : 0337); The Souls of Black Folk; United States; William Edward Burghardt Du Bois; États-Unis